2020
DOI: 10.1177/1525740120915205
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Language Pathologists’ Perceived Competence in Working With Culturally and Linguistically Diverse Clients in the United States

Abstract: A clinician’s perceived competence determines his or her ability to attain clinical outcomes and persevere through challenging situations. This study examined the perceived competence of 337 speech-language pathologists (SLPs), including monolingual and bilingual, working with culturally and linguistically diverse (CLD) clients within the United States. Results indicated comparable competence levels of both monolingual and bilingual SLPs in their service delivery to monolingual English-speaking clients. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…SLPs also must be provided with opportunities to consider the role of language proficiency in their work with ELs in language/literacy development. Parveen and Santhanam's (2020) study pointed out that bilingual SLPs had more perceived competence than monolingual SLPs in working with ELs on assessment and intervention outcomes. Hence, providing monolingual SLP GSs with opportunities to better understand and implement instructional approaches with ELs reinforces the importance of collaborative work of bilingual and monolingual professionals.…”
Section: Pedagogical and Clinical Implicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…SLPs also must be provided with opportunities to consider the role of language proficiency in their work with ELs in language/literacy development. Parveen and Santhanam's (2020) study pointed out that bilingual SLPs had more perceived competence than monolingual SLPs in working with ELs on assessment and intervention outcomes. Hence, providing monolingual SLP GSs with opportunities to better understand and implement instructional approaches with ELs reinforces the importance of collaborative work of bilingual and monolingual professionals.…”
Section: Pedagogical and Clinical Implicationsmentioning
confidence: 97%
“…Many of the SLPs reported that they were not comfortable with assessing and/or providing services to EL students. Parveen and Santhanam (2020) examined the perceived competence of 337 monolingual and bilingual SLPs who were working with ELs within the United States. Their survey consisted of three sections: background information, training received on serving ELs, and SLPs' perceived competence in their service delivery to this population.…”
Section: Working With Els: Perceived Knowledge Competencies and Self-...mentioning
confidence: 99%
“…Recommendation: Foster and systematically develop linguistic differences. SLP curricula in the United States primarily focus on the linguistic aspects of communication disorders in English with little to no exposure to linguistically diverse client populations (Guiberson & Atkins, 2010;Hammer et al, 2004;Kohnert et al, 2003;Parveen & Santhanam, 2021). Students who speak languages other than English, who are much needed in our profession, should be given opportunities to integrate knowledge of their languages with the clinical skills they are acquiring in school (Kritikos, 2003;Santhanam & Parveen, 2018).…”
Section: Barrier: Access To the Graduate School Curriculummentioning
confidence: 99%
“…Although this is a mandate, the lack of bilingual and multilingual SLPs creates a situation where many families have lack of information and communication due to the initial language barrier. Given this, when the SLP and client/ student speak the same language, there is a greater probability of more success as there is a greater ability to work and communicate with these students (Parveen & Santhanam, 2020).…”
Section: Diagnosing and Treating Bilingual Studentsmentioning
confidence: 99%
“…SLPs may believe that students are unmotivated to work on speaking in their L2; however, many times this is not the case. It has been found that students are less willing to talk and collaborate when they cannot relate to, or communicate entirely with, their provider (Parveen & Santhanam, 2020). These aspects play an essential role in the diagnosis process as well as in the therapy provided to students.…”
Section: Diagnosing and Treating Bilingual Studentsmentioning
confidence: 99%